PREPARATION OF BINARY INCLUSION COMPLEX OF RIVAROXABAN WITH BETA CYCLODEXTRIN; PHYSIOCHEMICAL AND SOLID-STATE CHARACTERIZATION - Waqas Haider Khan; Ikram Ullah Khan; Sajid Asghar; Muhammad Irfan; Syed Haroon Khalid (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Low aqueous solubility and erratic bioavailability pattern is the limiting factor to achieve desired therapeutic outcomes from a variety of new and existing drugs. This study was aimed to evaluate the effect of the preparation method on the binary inclusion complex of rivaroxaban (RIV). The inclusion complexes were prepared using four different methods (physical trituration, freeze drying kneading and solvent evaporation) at RIV-cyclodextrins weight molar ratios of 1:1, 1:2 and 1:4. Solubility studies in the presence of βCD was performed to determine the quantitative increase in solubility. Dissolution studies were performed to evaluate the drug release behavior from the binary inclusion complex in the aqueous medium. The inclusion complexes were subjected to characterization of fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffractometry (XRD) and differential scanning calorimetry (DSC). The phase solubility studies confirmed that RIV solubility ameliorated proportionally with an increase in β-CD concentration. FTIR, SEM, XRD and DSC confirmed the successful inclusion of RIV into cyclodextrin (β-CD) cavity. Among the four preparation methods (physical trituration, freeze drying kneading and solvent evaporation) used for the inclusion complexes, kneading is the most suitable method for preparation of RIV: βCD inclusion complex with ameliorated solubility and drug release in aqueous medium.